The effect of selective exposure on agenda diversity: An experimental analysis of high-choice media environments and issue consensus - Wagner, John K. (Frontiers in Political Science, 2023)
In the age of the high-choice media environment, there is less and less consensus over America's most important problem. Over the last two decades, several studies have demonstrated that agenda diversity—the degree of disagreement over the most important issue—has grown drastically in the U.S. Despite the importance of public consensus in the policy process and for representation, we lack a causal understanding of the mechanisms underpinning changes in agenda diversity. This paper hypothesizes that selective exposure causes greater agenda diversity, as individuals avoid news on issues they are less interested in. This study leverages an experiment (N = 433) to investigate the effect of varying levels of selectivity in the media environment on individual-level agenda diversity. Results support the notion that a media environment that allows for selective exposure compared to forced exposure more typical of the broadcast-era results in higher agenda diversity. These findings support the theory that rising levels of media selectivity contribute to a rise in agenda diversity. The implications of an increasingly diverse national agenda are discussed.